Optimizing Online Learning Resource to Improve Students’ Autonomous Learning and Vocabulary Mastery through Word Wall Activities - Ilzam Dhaifi, Punaji Setyosari, Utami Widiati, Saida Ulfa (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2020)
The rapid development of the internet provides many opportunities for humans to develop, including in the field of education. This study explores the great benefits of the internet as an online learning resource combined with students’ autonomous learning for vocabulary acquisition. This study used a quasi-experimental approach, the research subjects were two groups who received different treatments, the experimental group used reading materials on the internet that were selected easily based on student interests, students were asked to make simple notes on the worksheets and do word wall activities. Meanwhile, the control group used conventional methods for vocabulary mastery. Based on the results of the posttest, it is known that the experimental group has better vocabulary mastery than students in the control group, and students in the experimental group who have high autonomous learning get better vocabulary mastery than students with low autonomous learning. The conclusion of this study shows that reading short stories on the internet which are selected based on student interest contributes to better vocabulary mastery for students. Students with high autonomous learning have a higher interest in exploring vocabulary mastery using short stories on the internet. The use of the internet is able to stimulate student interest in improving word mastery in word wall media activities. The use of the internet as a source of learning English online is able to solve classic problems in boring language classes.